Estimation of Carbon Sequestration in Macadamia Nut in Kaski District, Nepal - Timilsina, A. P.; Gairhe, A.; Malla, G.; Paudel, B.; Rimal, R.; Bhandari, R. (Journal of Agriculture and Environment, 2019)
Available with full text.